Microtomografia computadorizada aplicada à endodontia: otimização de parâmetros físicos e aplicações práticas - Santos, Bernardo Camargo dos (2019)
This thesis aims to optimize the application of microCT in teeth seeking the best image quality from the acquisition to thresholding, arguing over the spatial resolution, contrast and noise. For this, the resulting images of three different micro-tomography devices were compared qualitatively and quantitatively, with different acquisition energy powers and arrangements, after the use of different image processing algorithms, as filters and thresholding methods. It was demonstrated that the simple use of the same acquisition parameters is not sufficient for the correct interpretation, comparison, and replication of the results obtained between different devices, requiring an standard approach. A positive relationship between the decrease of the beam voltage and the quality and amount of visualized structures was shown. The use of the Unsharp mask filter significantly improved the segmentation quality of the root canals, in addition to reducing their variance in relation to the raw image. The best images were provided by a semi-automatic thresholding method. However, more consistent results were shown using the automatic method developed by Otsu in three-dimensional space.